2020
DOI: 10.3390/ijerph17239101
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adverse Drug Reactions in Patients with End Stage Renal Disease in Greece

Abstract: Background: Patients with end-stage renal disease (ESRD) require specialized therapeutic interventions. The decreased renal function that modulates the physiology and presence of comorbidities is often associated with variations in the pharmacological response, thus increasing the risk of adverse drug events or reactions (ADE/ADRs) from co-administered drugs. Methods: A cross-sectional study to record comorbidities, drug–drug interactions (DDIs), ADE/ADRs in patients with chronic kidney disease of stage five i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…The analysis of the DDIs and their clinical significance have been previously presented [ 29 , 30 ]. Briefly, medication regimens were recorded and DDIs were detected using available online drug interaction checker tools (Medscape and Drugs.com; accessed on 1 April till 30 July 2022), considering the level of evidence available in the literature describing the significance, such as experts’ opinions, in silico, in vitro, in vivo data, clinical studies, reviews, the Summary of Product Characteristics (SmPC), and reports from regulatory authorities.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of the DDIs and their clinical significance have been previously presented [ 29 , 30 ]. Briefly, medication regimens were recorded and DDIs were detected using available online drug interaction checker tools (Medscape and Drugs.com; accessed on 1 April till 30 July 2022), considering the level of evidence available in the literature describing the significance, such as experts’ opinions, in silico, in vitro, in vivo data, clinical studies, reviews, the Summary of Product Characteristics (SmPC), and reports from regulatory authorities.…”
Section: Methodsmentioning
confidence: 99%
“…A study of patients with ESKD found that 75% of the cohort had potential drug-drug interactions, with approximately half of them classified as “serious” or “needing close monitoring”; they found a non-statistically significant association between the number of drug-drug interactions and the occurrence of ADEs. 17 Chronic PIMs are also associated with an increased length of hospital stay and a higher risk of death among patients with CKD of all stages. 18 , 19 As such, identifying and deprescribing PIMs are an important intervention to reduce pill burden, decrease individual and societal-level drug costs, improve quality of life, and decrease ADEs and premature or preventable death.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ADRs are prevalent, frequently serious, and potentially preventable in CKD patients [9]. Therefore, assessing the causality, severity, and preventability of ADRs is essential to reduce the likelihood of associated complications [10].…”
Section: Introductionmentioning
confidence: 99%